PRICES OF AGRICULTURE PRODUCTS AND MONETARY POLICY REACTION - Djukić, Mirko; Pjescić, Veselin; Vilaret, Snežana (Economics of Agriculture, 2009)
The primary goal of the National Bank of Serbia is achievement of y-o-y CPI growth within the target range. This measure of inflation contains a relatively high share of agriculture product prices, much larger than in the retail price index. Movements in agriculture product prices are very volatile and unpredictable, which makes the task of the National Bank of Serbia difficult. Effects of agriculture prices growth on inflation are divided into the first round effects (directly, through contribution of agriculture product prices in the inflation index and cost effects on processed food prices), and second round effects, through rise in inflation expectations and wages. Among monetary policy creators it is widely accepted that monetary policy should not react to the first round, but to the second round effects. Over the previous years, the National Bank of Serbia pursued monetary policy in line with this.